Identification of osteopontin as a biomarker of human exposure to fine particulate matter. (February 2019) - Ho, Chia-Chi; Wu, Wei-Te; Chen, Yu-Cheng; Liou, Saou-Hsing; Yet, Shaw-Fang; Lee, Chia-Huei; Tsai, Hui-Ti; Weng, Chen-Yi; Tsai, Ming-Hsien; Lin, Pinpin
Abstract: Ambient particulate matter (PM) exposure is associated with pulmonary and cardiovascular diseases; however, there is scant research linking data on animal and human cells. The objective of this study was to investigate these associations. Vascular remodeling plays a crucial role in both pulmonary and cardiovascular diseases. Therefore, we conducted a transcriptomic analysis using vascular smooth muscle cells (VSMCs) to identify potential regulators or markers of PM exposure. We demonstrated that fine and coarse PM increased VSMC proliferation in mice. We conducted a genome-wide cDNA microarray analysis, followed by a pathway analysis of VSMCs treated with coarse PM for durations of 24, 48, and 72 h. Sixteen genes were discovered to be time-dependently upregulated and involved in VSMC proliferation. Osteopontin (OPN) is indicated as one of the regulators of these upregulated genes. Both fine and coarse PM from industrial and urban areas significantly increased OPN expression in VSMCs and macrophages. Moreover, oropharyngeal instillation of fine and coarse PM for 8 weeks increased the VSMCs in the pulmonary arteries of mice. OPN level was consistently increased in the lung tissues, bronchoalveolar lavage fluid, and serum of mice. Moreover, we analyzed the plasma OPN levels of 72 healthy participants recruited from the studied metropolitan area. Each participant wore a personal PM2.5 sampler to assess their PM2.5 exposure over a 24 h period. Our results indicate that personal exposure to fine PM is positively correlated with plasma OPN level in young adults. The data obtained in this study suggest that exposure to fine and coarse PM may cause pulmonary vascular lesions in humans and that OPN level may be a biomarker of PM exposure in humans. Graphical abstract: Highlights: PM2.5 and PM2.5-10 increased OPN expression and VSMC proliferation in vitro. We verified PM2.5 and PM2.5-10 also increased OPN expression in mice. PM2.5 levels were associated with increased OPN levels in human. OPN may be the exposure biomarker for PM-induced pulmonary vascular lesions. Abstract : Osteopontin is identified as a biomarker of PM exposure in humans.